Recent Advances in Self-Exciting Photodynamic Therapy - Blum, Nicholas Thomas; Zhang, Yifan; Qu, Junle; Lin, Jing; Huang, Peng (Frontiers in Bioengineering and Biotechnology, 2020)
Photodynamic therapy (PDT) is already (Food and Drug Administration) FDA approved and used in the clinic for oncological treatment of pancreatic, lung, esophagus, bile duct, and of course several cancers of skin. It is an important tool in the oncological array of treatments, but for it exist several shortcomings, the most prominent of which is the shallow depth penetration of light within tissues. One-way researchers have attempted to circumvent this is through the creation of sself-exciting “auto-PDT” nanoplatforms, which do not require the presence of an external light source to drive the PDT process. Instead, these platforms are driven either through oxidative chemical excitation in the form of chemiluminescence or radiological excitation from beta-emitting isotopes in the form of Cherenkov luminescence. In both, electronic excitations are generated and then transferred to the photosensitizer (PS) via Resonance Energy Transfer (RET) or Cherenkov Radiation Energy Transfer (CRET). Self-driven PDT has many components, so in this review, using contemporary examples from literature, we will breakdown the important concepts, strategies, and rationale behind the design of these self-propagating PDT nanoplatforms and critically review the aspects which make them successful and different from conventional PDT. Particular focus is given to the mechanisms of excitation and the different methods of transfer of excited electronic energy to the photosensitizer as well as the resulting therapeutic effect. The papers reviewed herein will be critiqued for their apparent therapeutic efficiency, and a basic rationale will be developed for what qualities are necessary to constitute an “effective” auto-PDT platform.